(untitled) (Eduscotech, 2019)
The aim of this research was to study the effect of peeling of cassava to the cyanogenic glucosides content on the glucose syrup production process enzymatically. This research was performed by treatment with cassava peeling of the outer skin and the inner skin. Furthermore slurry was made ​from​ cassava conditioned at pH 5; 5.5, and 6, the temperature 40°C. Then the observation of cyanogenic glucosides after hydrolyzed with α-amylase. The results showed that the cyanogenic glucoside content was not showing reduction in the safety level for all treatments which indicated the containing still high above 400 ppm in the glucose syrup. So, peeling of cassava skin didn’t enough for reducing cyanogenic glucoside content.